1990
DOI: 10.1002/glia.440030106
|View full text |Cite
|
Sign up to set email alerts
|

Expression of glial fibrillary acidic protein (GFAP) in goldfish optic nerve following injury

Abstract: By using an antibody to goldfish glial fibrillary acidic protein (GFAP), the reaction of goldfish optic nerve to injury has been studied by immunoblotting and immunohistochemical methods. Goldfish optic nerve, which normally lacks GFAP immunoreactivity (Nona et al.: Glia, 2:189-200, 1989), expresses GFAP following injury. This immunoreactivity, which is observed as early as 10 days after crush and which is still evident at 30 days after crush, all but disappears by 150 days after crush. Since it is well establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
2

Year Published

1991
1991
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 61 publications
1
29
0
2
Order By: Relevance
“…Anders and Johnson (1990) GFAP immunoreactivity in the piriform cortex returned to control levels. Similarly, Stafford et al (1990) reported the appearance of GFAP+ processes in goldfish optic nerve following nerve crush. No GFAP labeling was found after the nerve had regenerated.…”
Section: Comparison To Other Glial Reactionsmentioning
confidence: 87%
“…Anders and Johnson (1990) GFAP immunoreactivity in the piriform cortex returned to control levels. Similarly, Stafford et al (1990) reported the appearance of GFAP+ processes in goldfish optic nerve following nerve crush. No GFAP labeling was found after the nerve had regenerated.…”
Section: Comparison To Other Glial Reactionsmentioning
confidence: 87%
“…Duffy et al 1992;McClellan 1992;Nona and Stafford 1995;Benraiss et al 1997) following numerous types of injury (e.g. Simpson 1964; Anderson and Waxman 1981;Stafford et al 1990). The regenerated neural tissue has been reported to be enclosed by meningeal tissue, in the goldfish, Carassius (Bernstein and Bernstein 1967), the frog, Xenopus (Michel and Reier 1979) and the lizard, Anolis (Simpson 1983), but little is known of the role of these meningeal cells in the regenerative process.…”
Section: Introductionmentioning
confidence: 99%
“…Such impediments for axonal regeneration are apparently absent from the fish optic nerve, where astrocytic scars do not develop (Wolburg and Kastner, 1984;Stafford et al, 1990). Biochemical analysis showed that fish oligodendrocytes and CNS myelin lack the proteins that inhibit axon growth in mammals .…”
mentioning
confidence: 99%